CAUSES ET EFFETS DE L’EXODE RURAL SUR LE DÉVELOPPEMENT SOCIOÉCONOMIQUE DANS LE TERRITOIRE D’OPALA. CAS DE SECTEUR DES TOOLI (RDC). - ASAKA John, ANGONDO; Joseph BOKUMBE WASSA,; Christophe ATWAIWANI LIKONO,; Guy BUSE MOLISHO,; Prosper BOMBULA MOSALA,; Willy KPENZU NGUNDE,; Prosper IDJUMBE WOLA, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The present survey is about the analysis of lasting displacement of populations leaving the Sector of the Toolis (farming Zone) to be going to become implanted in the City of Kisangani and/or to the hinterland of the City. The pauperization of the countries creates more and more marginal and not only reinforce the motives of desertion on behalf of the peasants but also of other types of workers. The exodus provokes pauperization to the individual level, as to the scale of the country. Every peasant in flight is a lack to win for the state (Sector). The objectives pursued in this survey are, to know how to Identify the reasons of the farming exodus, to determine the people who practice the farming exodus and to clear the consequences that ensue some, The farming exodus results from the setting up of factors of dismissal and the factors of attraction. The city offers many gainful jobs, and of the more elevated salaried employees. The city answers the social and cultural aspirations better, notably to the eyes of the young generations: more open social environment, more free, less coercive than the traditional farming setting, easier access to the education and, leaving, to the social ascension. With this phenomenon, the Sector of the Toolis is deprived of the active population, presenting a weak enough production. The farming exodus nourishes meaningful way: A phase of industrialization with the one-handed availability of important work hired in the shops and the factories;The movement of urbanization with the development of the outskirts of the cities.Most these isolated volunteers have been disappointed of their arrival in the city of Kisangani, here is why, not finding jobs imagined to the departure, they withdrew once again from the city of urban Kisangani(exode) to live precisely to the hinterland of the city of Kisangani in Kubagu,Ngenengene, LokeleLokele,Alibuku,Maweda, Lula,…La majority of the citizens is of small poor peasants and in precarious situation. They revolt repeatedly.